Spiny neurons of amygdala, striatum, and cortex use dendritic plateau potentials to detect network UP states - Oikonomou, Katerina D.; Singh, Mandakini B.; Sterjanaj, Enas V.; Antic, Srdjan D. (Frontiers in Cellular Neuroscience, 2014)
Spiny neurons of amygdala, striatum, and cerebral cortex share four interesting features: [1] they are the most abundant cell type within their respective brain area, [2] covered by thousands of thorny protrusions (dendritic spines), [3] possess high levels of dendritic NMDA conductances, and [4] experience sustained somatic depolarizations in vivo and in vitro (UP states). In all spiny neurons of the forebrain, adequate glutamatergic inputs generate dendritic plateau potentials (“dendritic UP states”) characterized by (i) fast rise, (ii) plateau phase lasting several hundred milliseconds and (iii) abrupt decline at the end of the plateau phase. The dendritic plateau potential propagates towards the cell body decrementally to induce a long-lasting (longer than 100 ms, most often 200 – 800 ms) steady depolarization (~20 mV amplitude), which resembles a neuronal UP state. Based on voltage-sensitive dye imaging, the plateau depolarization in the soma is precisely time-locked to the regenerative plateau potential taking place in the dendrite. The somatic plateau rises after the onset of the dendritic voltage transient and collapses with the breakdown of the dendritic plateau depolarization. We hypothesize that neuronal UP states in vivo reflect the occurrence of dendritic plateau potentials (dendritic UP states). We propose that the somatic voltage waveform during a neuronal UP state is determined by dendritic plateau potentials. A mammalian spiny neuron uses dendritic plateau potentials to detect and transform coherent network activity into a ubiquitous neuronal UP state. The biophysical properties of dendritic plateau potentials allow neurons to quickly attune to the ongoing network activity, as well as secure the stable amplitudes of successive UP states.